A novel pattern‐reconfigurable grid array antenna. Issue 8 (16th April 2019) - Yan, Ji; Liu, Xueguan; Liu, Changrong; Hu, Shuting
Abstract: This article presents the design of a grid array antenna with pattern reconfigurable ability. Discussion of various factors that affect the radiation pattern is presented. Interdigital structure, which serves as short radiation line of grid array antenna is then introduced to reconfigure radiation pattern. Change of main beam direction is realized via state change of PIN diodes loaded in interdigital structure and variation of feed point. The scanning angle varies from −33° to +38° and the average gain is about 10 dBi. The proposed antenna was fabricated and measured. Measured results show the proposed antenna possesses good beam‐scanning characteristics and has potential value in long‐distance power supply for various passive nodes.